Rapid detection and discrimination of chromosome- and MCR-plasmid-mediated resistance to polymyxins by MALDI-TOF MS in Escherichia coli: the MALDIxin test. (1st September 2018) - Dortet, Laurent; Bonnin, Remy A; Pennisi, Ivana; Gauthier, Lauraine; Jousset, Agnès B; Dabos, Laura; Furniss, R Christopher D; Mavridou, Despoina A I; Bogaerts, Pierre; Glupczynski, Youri; Potron, Anais; Plesiat, Patrick; et al.
Abstract: Background: Polymyxins are currently considered a last-resort treatment for infections caused by MDR Gram-negative bacteria. Recently, the emergence of carbapenemase-producing Enterobacteriaceae has accelerated the use of polymyxins in the clinic, resulting in an increase in polymyxin-resistant bacteria. Polymyxin resistance arises through modification of lipid A, such as the addition of phosphoethanolamine (pETN). The underlying mechanisms involve numerous chromosome-encoded genes or, more worryingly, a plasmid-encoded pETN transferase named MCR. Currently, detection of polymyxin resistance is difficult and time consuming. Objectives: To develop a rapid diagnostic test that can identify polymyxin resistance and at the same time differentiate between chromosome- and plasmid-encoded resistances. Methods: We developed a MALDI-TOF MS-based method, named the MALDIxin test, which allows the detection of polymyxin resistance-related modifications to lipid A (i.e. pETN addition), on intact bacteria, in <15 min. Results: Using a characterized collection of polymyxin-susceptible and -resistant Escherichia coli, we demonstrated that our method is able to identify polymyxin-resistant isolates in 15 min whilst simultaneously discriminating between chromosome- and plasmid-encoded resistance. We validated the MALDIxin test on different media, using fresh and aged colonies and show that it successfully detects all MCR-1 producers in a blindly analysed set of carbapenemase-producing E. coli strains. Conclusions: The MALDIxin test is an accurate, rapid, cost-effective and scalable method that represents a major advance in the diagnosis of polymyxin resistance by directly assessing lipid A modifications in intact bacteria.